2014
DOI: 10.1002/tox.22023
|View full text |Cite
|
Sign up to set email alerts
|

Hinokitiol induces autophagy in murine breast and colorectal cancer cells

Abstract: Hinokitiol is found in the heartwood of cupressaceous plants and possesses several biological activities. Hinokitiol may play an important role in anti-inflammation and antioxidant processes, making it potentially useful in therapies for inflammatory-mediated disease. Previously, the suppression of tumor growth by hinokitiol has been shown to occur through apoptosis. Programmed cell death can also occur through autophagy, but the mechanism of hinokitiol-induced autophagy in tumor cells is poorly defined. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 19 publications
2
35
0
2
Order By: Relevance
“…It is a naturally occurring, aromatic, seven-membered tropolone compound. It has been reported to have applications in regulating several biological properties [24,25,35], and has also been shown to have inhibitory effects in several cancer cell lines [24,36,37]. In previous studies, the effective dose of hinokitiol against cancer cells ranged from 5 to 200 μM [37].…”
Section: Resultsmentioning
confidence: 99%
“…It is a naturally occurring, aromatic, seven-membered tropolone compound. It has been reported to have applications in regulating several biological properties [24,25,35], and has also been shown to have inhibitory effects in several cancer cell lines [24,36,37]. In previous studies, the effective dose of hinokitiol against cancer cells ranged from 5 to 200 μM [37].…”
Section: Resultsmentioning
confidence: 99%
“…Hinokitiol was also indicated to cause caspase-dependent apoptosis (16) and differentiation (17) in teratocarcinoma F9 cells. A recent study indicated that hinokitiol induced autophagy in murine breast and colorectal cancer cells via downregulation of the v-akt murine thymoma viral oncogene homolog 1/mechanistic target of rapamycin (serine/threonine kinase) signaling pathway, which led to cell death (18). Although the anti-tumor activity of hinokitiol has been reported, its effect on CSCs remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that enhancing the degradation of EGFR may provide a promising approach in cancer treatment (25). It has additionally been demonstrated that hinokitiol is able to cause death of breast cancer cells via induction of autophagy (18). Huang et al (40) demonstrated that hinokitiol may inhibit the expression of matrix metalloprotease-1 through the reduction of nuclear factor-κB (NF-κB) activation, resulting in the suppression of metastasis in a mouse melanoma model.…”
mentioning
confidence: 99%
“…Sua capacidade de agir na caspase-9 faz com que haja bloqueio no ciclo celular; ainda, o composto induz dois tipos de morte celular, tanto por apoptose, quanto por autofagia, por meio da ativação da via de sinalização Akt/mTOR, o que reduz o crescimento celular in vitro das células de câncer de mama e câncer colorretal (WANG et al 2016). …”
Section: Hinokitiolunclassified
“…Já a nobiletina, um flavonóide natural encontrado na casca das frutas cítricas como a tangerina, possui atividade angiogênica conhecida e, em células MCF-7, foi capaz de inibir a angiogênese tumoral (WANG et al 2016).…”
Section: Outras Substâncias Com Importante Papel No Tratamento Do Cânunclassified